Time-frequency analysis of simulated binary pulsar signals - Nandhini Ganesan (2013)
The science that deals with the study of celestial objects, the physics, chemistry and evolution of such objects is called Astronomy and the branch of Astronomy that deals with the behavior and dynamic processes of the celestial objects is called Astrophysics. This dissertation discusses one such discoveries of the modem astronomy, Pulsars. Pulsar, from the time it was discovered in 1967 has been a curious and exciting topic for the entire astrophysicist. They are perhaps the most extraordinary Physics laboratory in the Universe. With its discovery by Jocelyn Bell Burnell and Antony Hewish, who received Nobel Prize in 1974, it got the attention of many astrophysicists. Pulsars are used to detect gravitational waves and they earned another Nobel Prize in 1993 for a prediction related to the same. In order to search pulsars, many methods have been employed. One common method used to detect the Binary pulsar is called sideband search. Sideband search employs Two-stage Fourier Analysis for the detection. This dissertation aims to use Autocorrelation method instead of Two-stage Fourier analysis for the detection of Orbital period of the pulsar. The performance of both the methods is compared using different Signal to Noise Ratio (SNR) values and is shown to be similar. Time frequency analysis is done on the pulsar signal to estimate the Instantaneous Frequency. From Instantaneous Frequency (IF), the pulsar velocity and acceleration are estimated. It is used to characterize the pulsar and extract two relevant orbital parameters in circular orbit. Thus the study of pulsars enables us to understand the origin of our Universe, test the theory of Einstein's relativity. Because of pulsars our timing standard has improved and